2010
DOI: 10.1155/2010/740140
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance ofNOTCH1andFBXW7Mutations in Pediatric T-ALL

Abstract: Abstract. The NOTCH signaling pathway plays important role in the development of multicellular organisms, as it regulates cell proliferation, survival, and differentiation. In adults, it is essential for the T-or B-lymphocyte lineage commitment. NOTCH1 and FBXW7 mutations both lead the activation of the NOTCH1 pathway and are found in the majority of T-ALL patients. In this study, the mutation analysis of NOTCH1 and FBXW7 genes was performed in 87 pediatric T-ALLs who were treated on the ALL-BFM protocols. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 50 publications
4
33
1
Order By: Relevance
“…Thus, the primary objective of this study was to search for valid stratification criteria for patients with T-LBL. Here, we analyzed the mutational status in BLOOD, 18 APRIL 2013 x VOLUME 121, NUMBER 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the primary objective of this study was to search for valid stratification criteria for patients with T-LBL. Here, we analyzed the mutational status in BLOOD, 18 APRIL 2013 x VOLUME 121, NUMBER 16 …”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, activating mutations of NOTCH1 and/or FBXW7 (N/F pos ) have been observed in about 50% of pediatric patients with T-cell lymphoblastic leukemia (T-ALL; for a complete overview of publications dealing with this topic, see supplemental Table 1 on the Blood website). [9][10][11][12][13][14][15][16][17][18][19] The evolutionary highly conserved NOTCH1 signaling pathway is involved in the regulation of many cellular processes; for example, early T-cell development. 20,21 The transmembrane protein NOTCH1 is activated by the contact of NOTCH1-ligands (Delta-like 1-4, Jagged1, or Jagged2), which trigger the proteolytic cleavages releasing the protein's active part, intracellular NOTCH1 (ICN1).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of correctly controlling Notch ICD half-life and the role of Fbxw7 in this process is also underscored by the fact that NOTCH1 and FBXW7 mutations can be found in T-cell acute lymphoblastic leukemia (T-ALL) (Erbilgin et al, 2010;Malyukova et al, 2007). In T-ALL patients, gain-of-function mutations in NOTCH1 are found in more than 50% of cases (Weng et al, 2004) and loss-of-function mutations in FBXW7 have also been described (Malyukova et al, 2007;Mansour et al, 2009;O'Neil et al, 2007).…”
Section: Regulation Of Notch Icd By Ubiquitylationmentioning
confidence: 99%
“…It has recently been shown that serum-and glucocorticoid-inducible kinase (SGK1) forms a trimeric complex with Notch ICD and Fbxw7, thereby enhancing Fbxw7-mediated Notch degradation (Mo et al, 2011). Functionally, Fbxw7 has been shown to be important in the control of stemness and neuronal fate versus glial differentiation in the developing brain (Matsumoto et al, 2011).The importance of correctly controlling Notch ICD half-life and the role of Fbxw7 in this process is also underscored by the fact that NOTCH1 and FBXW7 mutations can be found in T-cell acute lymphoblastic leukemia (T-ALL) (Erbilgin et al, 2010; Malyukova et al, 2007). In T-ALL patients, gain-of-function mutations in NOTCH1 are found in more than 50% of cases (Weng et al, 2004) and loss-of-function mutations in FBXW7 have also been described (Malyukova et al, 2007;Mansour et al, 2009;O'Neil et al, 2007).…”
mentioning
confidence: 99%
“…Translocation and mutations in Notch1 may alter its function and result in overexpression and independent activation, and *60% of T-ALL cases show an increased Notch1 activity (Asnafi et al, 2009;Erbilgin et al, 2010;Koch and Radtke, 2011). The effect of Notch1 activation on the T-ALL outcome is controversial.…”
Section: The Relative Gene Expression Pattern Characteristics Of T-almentioning
confidence: 99%